Sesame Uganda: Climate change risks and opportunities - Demissie, Teferi Dejene; Duku, Confidence; Groot, Annemarie; Oroma, George W.; Osumba, Joab J.L.; Budding-Polo, Monserrat; Lyimo, Raymond; Schonenberg, Pierre (2019)
Uganda’s agricultural sector is an important catalyst for economic growth, poverty alleviation, and food security. Nevertheless, the economic losses from the impacts of climate change on the agricultural sector by 2050 are estimated to be about US$1.5 billion (Zinyengere et al., 2016). Climate-smart agriculture (CSA) practices present an opportunity to reduce such losses, build resilience in the agriculture sector, improve productivity and farmer incomes, and contribute to climate change mitigation (CIAT & World Bank, 2017). In 2010, Uganda was the fifth largest producer of sesame globally, and production peaked at about 216,000 mega tonnes in 2012 (FAOSTAT, 2018). The average yield of sesame is about 700 kilograms per hectare (FAOSTAT, 2018).